1992
DOI: 10.1190/1.1443214
|View full text |Cite
|
Sign up to set email alerts
|

Detection and measure of the shear‐wave birefringence from vertical seismic data: Theory and applications

Abstract: An original method is presented that allows us to measure the local shear-wave birefringence properties over any depth interval. It requires the acquisition of two shear-wave vertical seismic profiles (VSPs), each with different initial polarizations of the shear wave. The method is based on the estimation of a two by two matrix (called the propagator matrix) that represents a linear operator between two states of polarization. No information is required about layering above the zone of interest (in particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…Since elastic information is derivable from seismic data via AVO inversion, then the in-situ stress state can be estimated from anywhere where seismic waves have intersected the rocks at a wide (>40°) angle. Furthermore, the anisotropic stress equations of Iversen (1995) can be recast using parameters from linear slip theory (Schoenberg and Sayers, 1995), which can be derived from wide-angle, wide-azimuth, 3D seismic data (e.g., Lefeuvre et al, 1992;Varela et al, 2009), as shown here.…”
Section: Introductionmentioning
confidence: 99%
“…Since elastic information is derivable from seismic data via AVO inversion, then the in-situ stress state can be estimated from anywhere where seismic waves have intersected the rocks at a wide (>40°) angle. Furthermore, the anisotropic stress equations of Iversen (1995) can be recast using parameters from linear slip theory (Schoenberg and Sayers, 1995), which can be derived from wide-angle, wide-azimuth, 3D seismic data (e.g., Lefeuvre et al, 1992;Varela et al, 2009), as shown here.…”
Section: Introductionmentioning
confidence: 99%
“…Shear and compressional vibrators were used, with a far offset vertical vibrator used to provide signals for orientation of the three component downhole sonde. These data were then analyzed for the presence of shear wave splitting using the propagator matrix technique of Lefeuvre et al (1992).…”
Section: Methodsmentioning
confidence: 99%
“…This has been observed in both multicomponent seismic reflection data (Squires et al, 1989;Lewis et al, 1991), and vertical seismic profiles (VSPs) (Winterstein and Meadows, 1991). Although most processing techniques designed for multicomponent VSPs have taken into account polarization changes (e.g., Winterstein and Meadows, 1991;Lefeuvre et al, 1992;Zeng and MacBeth, 1993a), those designed for multicomponent seismic reflection data often assume constant polarization direction (e.g., Alford, 1986;Thomsen, 1988;Li and Crampin, 1993a).…”
Section: Introductionmentioning
confidence: 93%
“…The polarization direction of the leading split shear wave may give information about the orientation of in-situ stresses, and these stresses strongly affect several reservoir characteristics related to drilling, simulation and production (Bruno and Winterstein, 1994). In recent years, many processing techniques have been developed to estimate and interpret this polarization azimuth from recorded multicomponent seismic data (e.g., Alford, 1986;Thomsen, 1988;Winterstein and Meadows, 1991;Li and Crampin, 1993a;Lefeuvre et al, 1992;Zeng and MacBeth, 1993a, b;MacBeth et al, 1994). The polarization azimuth of the leading split shear wave, as related to the direction of the maximum in-situ stress, may vary both laterally with structural location and vertically with depth due to material properties, stratigraphy, bedding, and faults (Warpinski and Teufel, 1991).…”
Section: Introductionmentioning
confidence: 99%